Potential of Quercetin in Bitter Melon (Momordica charantia L) as an Antidiabetic: In Silico Study - Roni Yuliwar; I Ketut Sudiana; Kusnanto Kusnanto; Dwi Krihariyanie; Hidayat Arifin (Journal of Global Pharma Technology, 2020)
Purpose: The purpose of this study is to predict the in silico molecular interactions of bitter melon quercetin with GLP-1 receptors using the comparable compounds of myricetin and allosteric modulators. Methods: The in silico test was used to predict the quercetin molecular interactions by docking using the Molegro Virtual Docker computer program. The receptor used was human GLP-1, code PDB: 5VEX with allosteric modulators ligand (97V_1201 [A]). As part from predicting molecular interactions, this study also carried out the prediction of its pharmacokinetic properties (ADME) and the toxicity of quercetin and myricetin using the pkCSM online tool program. The data analysis was performed by comparing the docking bond energies between quercetin, the allosteric modulator ligands and the myricetin comparators at the target receptor. The lower the bond energy of the ligands to the target receptor, the more stable the bonds are. This can be used to predict the biological activity of the compound. Results: The in silico test results showed that the bond energy of quercetin = -70.2678 kcal/mol, myricetin = -105,298 kcal/mol and allosteric modulators = -126,992 kcal/mol. Conclusions: The above test results indicate that quercetin has antidiabetic potential by activating the GLP-1 receptor although it is lower than the myricetin and allosteric modulators. The results of the in silico test using the pkCSM online tool program showed that the quercetin compound had good pharmacokinetic properties and a low toxicity level.